2021
DOI: 10.24191/apmaj.v16i1-09
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and Determinants of the AAOIFI Financial Standards: Evidence from the MENA Region

Abstract: This paper analyses the level of compliance of financial disclosure with accounting standards of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and its determinants in Middle Eastern and North African (MENA) Islamic banks. Based on 40 Islamic banks in seven MENA countries over the period 2010-2016, the authors used a disclosure index to measure the compliance level and the effect of governance characteristics and the Sharia Board on the extent of compliance with the AAOIFI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…The highest score of SSB would lead to more monitoring and would improve firstly the transparency of the report, secondly the conformity with AAOIFI and thirdly the clients' confidence. This outcome is consistent with Nomran et al (2016), Mnif and Tahari (2020b), Bechihi et al (2021) and Ben Abdallah and Bahloul (2021). This outcome is consistent also with the agency theory, which claims that when SSB is efficient, it reduces agency conflicts.…”
Section: The Effect Of Governance On Disclosuresupporting
confidence: 87%
See 2 more Smart Citations
“…The highest score of SSB would lead to more monitoring and would improve firstly the transparency of the report, secondly the conformity with AAOIFI and thirdly the clients' confidence. This outcome is consistent with Nomran et al (2016), Mnif and Tahari (2020b), Bechihi et al (2021) and Ben Abdallah and Bahloul (2021). This outcome is consistent also with the agency theory, which claims that when SSB is efficient, it reduces agency conflicts.…”
Section: The Effect Of Governance On Disclosuresupporting
confidence: 87%
“…However, Mnif and Tahari (2020a) stipulated that BOD is not allied with disclosure because the IBs board members may be interested in studying Shariah law. Bechihi et al (2021) examined the compliance standard of the FD with AAOIFI of 40 IBs in seven MENA countries between 2010 and 2016. Using the FGLS [2] regression, the authors showed that the BOD's size has insignificantly negative connotation with financial disclosure.…”
Section: 24mentioning
confidence: 99%
See 1 more Smart Citation
“…Year Country Period Sample Methodology how banks operate in terms of sustainability. Bechihi et al (2021) found that gender diversity on the board had an impact on financial transparency. Othmani (2021) claims that the association between female representation and bank performance (that is evaluated through return on assets and return on equity) is direct.…”
Section: Author (S)mentioning
confidence: 99%
“…Mazzotta & Ferraro, 2020; Del Prete & Stefani, 2021) and in Germany(Berger et al, 2013;Berger et al, 2014), there were two studies in each, while in 12 studies the research was conducted in more than 1 country, so that in the study ofTran et al (2021), there is the largest sample of countries, i.e., 21 Western European countries. In 25 studies, the data Literature review of WoS studies of women in corporate governance in banking4 Women's impact on banking corporate governance According toBaklouti (2022), women on Sharia Supervisory Boards do not appear to have any effect on how Islamic banks financially perform Khan (2010). provides findings that indicate there is no significant relationship between corporate social responsibility reporting and the number of women serving on boards (CRS).…”
mentioning
confidence: 99%